Can complementary medicine enhance doctor-patient communication skills? Insights from an international medical student project. (December 2018) - Ortiz, M.; Teut, M.; Ben-Arye, E.; Reshef, A.; Kaffman, M.; Arnon, Z.; Stöckigt, B.; Bähr, V.; Meoded-Danon, L.; Brinkhaus, B.; Schiff, E.
Abstract: Introduction: Communication is an essential component of patient care, and although medical schools provide training on this topic, patients and physicians alike express the need to improve their communication skills. An international medical student collaboration explored whether complementary medicine (CM) has the ability to further enhance patient-doctor communication. Methods: Twenty-two medical students, nine mentors and two public representatives from Israel and Germany participated in this 18-month international group project. The goal was to explore CM methods that could enrich doctor-patient communication in several aspects. The group eventually chose to focus on four CM modalities, which included Chinese medicine; Mind-Body medicine; Touch therapies; Mindfulness and Herbal medicine. One workshop took place in Haifa and two workshops in Berlin, with continued inter-group work in-between. The workshops included interactive group formats such as "World Café", self-experience sessions in CM, working in small groups and delivering presentations to the entire group. Results: Besides benefitting from cultural exchange and networking, students learned various aspects of CM, with a particular focus on their relevance for enriching their communication skills. The main CM aspects that were highlighted included patient characterization in the context of Chinese medicine diagnosis, mindfulness, anamnesis regarding herbal use, and a physical exam based on concepts from touch therapies. Students summarized and condensed their observations into five educational modules, which are available online:http://www.b-zion.org.il/pages_e/6683.aspx . Conclusion: The cultural exchange and explorative process in this international medical student collaboration led to insights regarding the potential contribution of CM to patient-doctor communication. The outcomes of this international collaboration, specifically the educational modules it produced, should be further explored by medical schools, and assessed in clinical trials.